Frequency of Extrapulmonary TB among Human Immunodeficiency Virus (HIV) patients at Lady Reading Hospital, Peshawar - Abdur Rehman, Muhammad Bilal, Yaseen Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Human immunodeficiency virus/acquired immunodeficiency syndrome (AIDS) has now infected nearly 80 million people around the world since it first appeared. The HIV epidemic has had a profound effect on the global tuberculosis (TB) crisis attributing to 20% of all AIDS-related deaths. Less than one-tenth of one percent of Pakistan's population was estimated to have HIV. However, Pakistan has gone from having a low HIV prevalence to a high HIV epidemic. Pakistan is the sixth most problematic country in the world for TB because it accounts for about 63% of the TB load in the Eastern Mediterranean Region. Aim: To determine the prevalence of extrapulmonary tuberculosis among HIV patients. Study design: Prospective, cross-sectional study. Place and duration of study: Department of Medicine, Lady Reading Hospital, Peshawar from 17th April 2020 to 16th October 2020. Methodology: Seventy eight HIV patients were recruited to determine the frequency of extrapulmonary tuberculosis. Results: There were 34.6% males and 65.4% females with mean age was 45.44±5 years. The frequency of extrapulmonary tuberculosis in HIV was found to be 44.9%. Conclusion: Extrapulmonary tuberculosis is a significant problem among human immunodeficiency virus patients.